Development of a Single-Step Subtraction Method for Eukaryotic 18S and 28S Ribonucleic Acids. (25th June 2011) - Archer, Marie J.; Lin, Baochuan
Abstract : The abundance of mammalian 18S and 28S ribosomal RNA can decrease the detection sensitivity of bacterial or viral targets in complex host-pathogen mixtures. A method to capture human RNA in a single step was developed and characterized to address this issue. For this purpose, capture probes were covalently attached to magnetic microbeads using a dendrimer linker and the solid phase was tested using rat thymus RNA (mammalian components) with Escherichia coli RNA (bacterial target) as a model system. Our results indicated that random capture probes demonstrated better performance than specific ones presumably by increasing the number of possible binding sites, and the use of a tetrame-thylammonium-chloride (TMA-Cl-) based buffer for the hybridization showed a beneficial effect in the selectivity. The subtraction efficiency determined through real-time RT-PCR revealed capture-efficiencies comparable with commercially available enrichment kits. The performance of the solid phase can be further fine tuned by modifying the annealing time and temperature.